Potassium Titanate Assembled Titanium Dioxide Nanotube Arrays Endow Titanium Implants Excellent Osseointegration Performance and Nerve Formation Potential - Zhao, Hang; Liu, Feng; Yin, Yixin; Wang, Shuhua (Frontiers in Chemistry, 2022)
Titanium based materials have been widely applied in bone-tissue engineering. However, inefficient bone repair remains to be solved due to the lack of neural network reconstruction at the bone-implant interface. Herein, we propose a functional surface modification approach to promote neurogenesis. Using an electrochemical technique and a hydrothermal approach, a potassium titanate nanorod-decorated titanium oxide (K2Ti6O13-TiO2) nanotube array is constructed on the surface of titanium implants. The K2Ti6O13-TiO2 hybrid nanotube array on titanium implants can enhance the osteogenic differentiation of mesenchymal stem cells due to the special nanostructures of titanium oxide nanorods. Meanwhile, the release of potassium ions is able to accelerate the neural differentiation of neural stem cells. This study provides a new approach to promote neuralization on the surface of implants, which is promising for future applications in constructing a fully functional interface in bone repair.